The power of state : the cycle of the protest in Xinjiang, China. - Lim, Germaine Mei Jun. (2011)
The ethnic tension in Xinjiang, China is not built up in just one day. Rather, the Chinese State has been facing hostile standoff, which at times accelerated into violent rioting between the Uyghur and the Han Chinese, for decades. Yet, why is it that despite decades of long protest, the Uyghur is still unable to replace the Han Chinese ruling government in Xinjiang? Thus, the significance of this research is seeking to understand why social ethnic movement can be produce and reproduce in Xinjiang, which in turns leads, us to examine the role of the Chinese state in having a vital role in this vicious cycle of hostility.